Pengaruh Kompetensi Aparatur Desa, Pengendalian Internal dan Pemanfaatan Teknologi Informasi terhadap Akuntabilitas Pengelolaan Dana Desa di Kecamatan Galesong Kabupaten Takalar - Mispa, Sitti; Mannang, Arifuddin; Rahmawati, Rahmawati (Tangible Journal, 2025)
This study aims to analyze the influence of village apparatus competence, internal control systems, and the utilization of information technology on the accountability of village fund management. The background of this research stems from the ongoing low accountability in village fund management in several areas, particularly in Galesong District, Takalar Regency, which is indicated by delayed financial reporting, inappropriate fund usage, and the underutilization of information technology and community participation. This research uses a quantitative approach with a survey method targeting village officials, including village heads, secretaries, and treasurers. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS. The results show that internal control systems and the use of information technology have a positive and significant effect on the accountability of village fund management. Meanwhile, the competence of village apparatus does not have a significant effect. These findings highlight the importance of strengthening internal control systems and optimizing information technology to improve accountability financial management village in Galesong District, Takalar Regency at 2025.